The Drive to Partnership : Aid Coordination, and the World Bank - Eriksson, John (Washington, DC: World Bank, 2013)
The report reviews the Bank's experience with aid coordination, which lies at the intersection of many development effectiveness challenges. While globalization has brought new opportunities for development rewards, poverty has increased, and concessional aid shrunk. In 1995, the Bank focused on enhanced development effectiveness, emphasizing on linkages with the development community. An evaluative research was undertaken in 1998/99, and since then, aid coordination, and partnership has intensified, through initiatives such as the Poverty Reduction Strategy Paper (PRSP), a process by which low-income countries are preparing PRSPs, and, efforts among developing agencies, and bilateral donors are being made. However, the report finds that many challenges still lie ahead, and, examines results-based conceptual frameworks, through the determinants of effective country-led aid coordination, and mutual responsibility under country leadership, through selected country experiences, measuring the quality of aid coordination. While the review concludes that the development community has been well-served by the Bank's leadership, the goal of country leadership remains elusive. Recommendations suggest that the Bank align aid coordination policies, and practices with the Comprehensive Development Framework's principles of ownership, and partnership; and, that country teams supporting consultative groups, work together with the government, and development partners to formulate a strategy for moving to country leadership.